Douglis-Nirenberg elliptic systems in Hörmander spaces - Zinchenko, T. N.; Murach, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We investigate Douglis-Nirenberg uniformly elliptic systems in R^n on the class of Hormander Hilbert spaces H^φ, where φ is an RO-varying function of scalar argument. An a priori estimate for solutions is proved, and their interior regularity is studied. A sufficient condition for these systems to have the Fredholm property is given.